Correlation Among Body Composition Parameters and Long-Term Outcomes in Crohn's Disease After Anti-TNF Therapy - Ando, Katsuyoshi; Uehara, Kyoko; Sugiyama, Yuya; Kobayashi, Yu; Murakami, Yuki; Sato, Hiroki; Kunogi, Takehito; Sasaki, Takahiro; Takahashi, Keitaro; Ueno, Nobuhiro; Kashima, Shin; Moriichi, Kentaro; et al. (Frontiers in Nutrition, 2022)
Background The impact of the body composition on the pathophysiology and clinical course of Crohn's disease (CD) has not been fully elucidated. Aims To reveal the correlations among body composition and long-term outcomes in CD after anti-TNF therapy. Methods Ninety-one patients who received anti-TNF therapy as their first biologic treatment were enrolled. The skeletal muscle index (SMI), visceral and subcutaneous fat area (VFA, SFA), and the ratio of the VFA to SFA (mesenteric fat index; MFI) at the 3rd lumbar level were measured using computed tomography (CT) imaging before the induction. The correlation among the body composition and outcomes were retrospectively analyzed. Results The 5-year cumulative secondary failure- and resection-free rates in patients with a low SMI (39.1% and 64.8%) were significantly lower than those with a high SMI (67.5% and 92.7%; p = 0.0071 and 0.0022, respectively). The 5-year cumulative secondary failure-free rate in the patients with low VF (45.0%) was significantly lower than that in those with high VF (77.6%; p = 0.016), and the 5-year cumulative resection-free rate in patients with a high MFI (68.9%) was significantly lower than that in those with a low MFI (83.0%; p = 0.031). Additionally, patients with low age and BMI had significantly lower cumulative secondary failure- and resection-free rates than those with high age and BMI (low age: 37.4% and 71.2%; high age: 70.7% and 88.9%; p = 0.0083 and 0.027, respectively) (low BMI: 27.2% and 64.8%; high BMI: 68.3% and 87.9%; p = 0.014 and 0.030, respectively), respectively. In the multivariate analyses, a low SMI was the only independent risk factor for secondary failure (hazard ratio [HR] 2.15, 95% confidence interval [CI] 1.04–4.44), while low age (HR 4.06, 95% CI 1.07–15.4), a low SMI (HR 4.19, 95% CI 1.01–17.3) and high MFI were risk factors for bowel resection (HR 4.31, 95% CI 1.36–13.7). Conclusion The skeletal muscle mass and ratio of visceral to subcutaneous fat were suggested to reflect the long-term clinical outcome and may be helpful as prognostic markers after anti-TNF therapy in CD.